Issues of Special Education in Romanian Schools - Bolborici, Ana-Maria; Bódi, Diana-Cristina (Revistia, 2022)
School managers, teachers, students, as well as their parents are faced with increasingly frequent attempts to integrate the diversity of pupils as a result of integration policies at national and European level. Educational needs of impaired persons require special attention. Is necessary to make steps should be taken to ensure access to education for each category of disabled person as part of the education system. Legislative framework in the field of special education Romania takes into account the legislation created by the international bodies on the education of persons with special educational needs, to which Romania has adhered. This paper presents aspects regarding the organization of educational support services dedicated to children, students and young people with special educational needs in mainstream schools in accordance with Romanian law; it also underlines the international legal framework of reference.This paper is part of a wider project that focuses on teacher training to optimize the integration of SEN pupils into the mainstream school; we used data collection methods, such as social document study and focus-group. An integrated and tailored approach is needed for children with SEN (special educational needs); focus-groups organized with primary school and gymnasium children, as well as with support teachers, revealed a number of adaptation issues from both sides (pupils with SEN and students with no problems). On the other hand, the itinerant teachers are assaulted by a series organization problems and it becomes impossible to provide support and assistance to children with special needs who are growing in numbers.Training of teachers is one of the most important pillars in the integration of all those involved in education, it is the way to optimize service organizations. Teacher training must respond to the real and complex needs of the beneficiaries, based on exploratory learning.In the final, will be presented and analyzed the main important problems faced by both teachers and pupils in the current educational context.
Keywords: special education; educational needs; integration policies; children; teachers